High Rise Buildings: Design, Analysis, and Safety: An Overview - Imad Shakir; Mohammed Ahmed Jasim; Sardasht S. Weli (International Journal of Architectural Engineering Technology, 2021)
High-rise buildings have been rapidly increasing worldwide due to insufficient land availability in populated areas and their primary role as essential buildings in modern cities and capitals. However, high-rise buildings are very complicated due to the huge number of structural components and elements unlike low-rise buildings, as well as these high-rise buildings demand high structural stability for safety and design requirements. This paper aims to provide brief information about high-rise buildings regarding the basic definition, safety features, structural stability, and design challenges. A brief description of existing structural systems that are available in the literature is presented to articulate a technical issue that has been widely reported, named, adopting an effective structural system for resisting lateral loads resulting from wind and seismic activities. Consequently, a general overview is presented that covers the behavior of various structural systems for different heights of high-rise buildings by implementing a number of nonlinear static procedure analyses (pushover) and nonlinear dynamic procedure analyses (for wind and earthquake loading). Finally, a critical review of the available simplified model and seismic energy base design are also presented. This paper is intended to help in the development and application of construction systems for high-rise buildings in the future.